Effects of aspirin on the long-term management of depression in older people: A double blind randomized placebo-controlled trial. - Berk, Michael. (Mol Psychiatry, 2021)
Late-life depression is common and often inadequately managed using existing therapies. Depression is also associated with increased markers of inflammation, suggesting a potential role for anti-inflammatory agents. ASPREE-D is a sub-study of ASPREE, a large multi-centre, population-based, double-blind, placebo-controlled trial of aspirin vs placebo in older Australian and American adults (median follow-up: 4.7 years) of whom 1,879 were depressed at baseline. Participants were given 100mg daily dose of aspirin or placebo. Depressive symptoms were assessed annually using the validated, self-rated short version of the Center for Epidemiological Studies Depression (CES-D-10) scale. There was a significant increase in depressive scores (0.6; 95% CI 0.2 to 0.9; Chi-square (1) = 10.37; p = 0.001) and a decreased score in the mental health component of a quality of life scale (−0.7; 95% CI −1.4 to −0.1; Chi-square (1) =4.74; p = 0.029) in the aspirin group compared to the placebo group. These effects were greater in the first year of follow-up and persisted throughout the study, albeit with small to very small effect sizes. This study failed to demonstrate any benefit of aspirin in the long-term course of depression in this community-dwelling sample of older adults over a 5-year period, and identified an adverse effect of aspirin in the course of depression in those with pre-existing depressive symptoms.